(untitled) (Research, Society and Development, 2020)
Glyphosate is a broad-spectrum active ingredient used in the control of annual and / or perennial weeds, has a post-emergent, non-selective and systemic action, widely used in agricultural activities, and is not different in the municipality of Teófilo Otoni. This study aims to study the consumption of glyphosate in the municipality during 2017 and 2018 and compare the consumption curve during the year and the most sold commercial products. Through field research at the Minas Gerais Institute of Agriculture (IMA), sales surveys were conducted on the basis of the pesticide trade control system (SICCA). There was no significant increase between the years, however variations can be noticed during the months of the year where the consumption increased with the highest rainfall during the period. However, the data found were inconsistent with the 2017 annual bulletin of the Brazilian Institute of Environment and Renewable Natural Resources (IBAMA). A more detailed study is proposed in the municipality to find out where the products are most used.